2019
DOI: 10.1055/s-0039-1683977
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Patient Outcomes for Robotic-Arm-Assisted versus Manual Total Knee Arthroplasty

Abstract: Although there are many studies on the alignment advantages when using the robotic arm–assisted (RAA) system for total knee arthroplasty (TKA), there have been questions regarding patient-reported outcomes. Therefore, the purpose of this study was to use this index to compare: (1) total, (2) physical function, and (3) pain scores for manual versus RAA patients. We compared 53 consecutive RAA to 53 consecutive manual TKAs. No differences in preoperative scores were found between the cohorts. Patients were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 13 publications
(14 reference statements)
0
61
0
4
Order By: Relevance
“…The group also evaluated outcomes at 1-year, and found the robotic-arm assisted cohort to have superior overall (p ¼ 0.03) and physical function score (p ¼ 0.02), as well as improvements in pain (p ¼ 0.06) when compared with the manual cohort. 10 In a large, multicenter prospective trial, patients who underwent RATKAs were all found to have substantially improved outcomes based on quality metrics including the Short Form-12 Questionnaire mental composite and physical composite scores, the Forgotten Joint Scores, and the Knee Society total and subscores. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group also evaluated outcomes at 1-year, and found the robotic-arm assisted cohort to have superior overall (p ¼ 0.03) and physical function score (p ¼ 0.02), as well as improvements in pain (p ¼ 0.06) when compared with the manual cohort. 10 In a large, multicenter prospective trial, patients who underwent RATKAs were all found to have substantially improved outcomes based on quality metrics including the Short Form-12 Questionnaire mental composite and physical composite scores, the Forgotten Joint Scores, and the Knee Society total and subscores. 7…”
Section: Discussionmentioning
confidence: 99%
“…RATKA for the operative management of knee osteoarthritis has consistently demonstrated excellent postoperative patient satisfaction. [7][8][9][10][11] RATKA platforms have the ability to integrate a preoperative computed tomography (CT) scan with robotic software, to develop a patient-specific operative plan. 12,13 This plan is then further enhanced in the operating room, with real-time haptic feedback helping guide bony cuts.…”
mentioning
confidence: 99%
“…Postoperative KSS were comparable between the two cohorts. A recent report 24 of improved total and physical function scores 1-year after RATKA compared with manual technique may indicate superior outcomes beyond the early recovery, but further studies are needed to confirm the observations of one center.…”
Section: Discussionmentioning
confidence: 96%
“… 11 It is not always clearly stated in rTKA studies how the implant was aligned or how balance was achieved or defined. 1 , 3 The authors suggest there should be a minimum reporting criterion for future rTKA studies to clearly define these methods to allow the results to be interpreted in context. Currently all data from rTKA studies are being amalgamated on the assumption of a homogeneous group of patients and this may not be the case.…”
mentioning
confidence: 99%